Integrasi Kurikulum Merdeka dalam Pembelajaran Pendidikan Agama Islam (PAI) - Faisal; Junaidi; Sileuw, Marwan (Indonesian Journal of Teaching and Teacher Education, 2023)
The Merdeka Belajar curriculum provides freedom of learning which is formulated according to the needs of each educational institution, which has differences in characteristics, content, application and results achieved. This curriculum integration is examined to unite the components and values in it as part of Islamic religious education. The method used in this research is a qualitative approach, by reviewing data from interviews, reducing data, compiling data in certain units and grouping data based on an arrangement based on research questions. The last stage carried out in this research is data validation. This research demonstrated that the integration of the independent curriculum in Islamic religious education learning is a process that significantly provides a positive space for students, teachers and the environment to learn according to educational goals. The integration also increases the religiosity of students in socializing and social relations. With the integration of an independent curriculum, it is hoped that it can provide a view to optimize student learning outcomes from differences in concepts, implementation and learning outcomes by Islamic education teachers. Not only in the school environment but also for the future.